Peningkatan Pemahaman Membangun Budaya Pola Hidup Sehat Dikalangan Remaja di Parupuk Tabing Kota Padang - Siti Nurhaliza; Wireziyan Fadhilla; Rafli Dwi Putra; Yulia Hanoselina (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Adolescents are in a critical phase of habit formation and identity development. However, many still lack awareness about the importance of a healthy lifestyle, including balanced nutrition, physical activity, and adequate rest. This outreach program aims to enhance adolescents' knowledge and awareness regarding healthy living as a preventive measure for long-term well-being. The program was carried out through lectures, discussions, and Q&A sessions at Musholla Namiroh Parupuk Tabing, Padang City, targeting participants aged 10–15 years. The results indicate an increase in participants’ understanding of healthy lifestyle concepts and a growing interest in adopting positive behavioral changes. This activity demonstrates that an interactive and practical approach in health education can effectively empower youth to become agents of change in their communities.